Lived Experiences of Women Department Heads in Higher Education: Challenges, Opportunities and Constraints - Malabanan, Jalaine Joyce V. (International Journal of Psychosocial Rehabilitation, 2020)
–The notion of a woman as a leader has been a polarizing topic for many years. Our society, a masculine society, have customarily perceived males to lead and we have been acculturated with this notion that it has been firmly entrenched in our norms. This study highlights the importance of the of Women Deans and Department Heads’ lived experiences and the value of listening to their perspectives, so as to offer insights into what has most helped and hindered their successes in their field. In order to gain a better understanding of these experiences, a qualitative phenomenological study, using Interpretative Phenomenological Analysis, was conducted to explore women leaders’ lived experiences and identify what they went through in their formal preparations prior to the ascending to the position, their role and responsibilities as middle managers and the experienced gender stereotypes and prejudices in carrying out their positions. The in depth analysis of the data showed that the participants’ leadership styles are unaffected by their gender, collaborative, and demonstrative of care and nurturing of students. They regard gender never as an issue and that women, like men, are qualified and have the capacity to excel in the area of leadership. Furthermore, the study revealed that these women leaders have dispelled the myth of the ‘Macho culture’ and broke the glass ceiling in the middle management of academic institutions as they believe that in terms of academic leadership, what gives rise to elevation is how one performed and not their genders.